Управління ризиками інвестиційного маркетингу на диверсифікованих підприємствах - Kalinin, Oleksandr; Gonchar, Viktoriya; Simanavičienė, Žaneta (Dr. Viktor Koval, 2019)
Introduction. In modern economic environment, obtaining financial stability in the long run is one of the conditions for competitive advantages. The condition for achieving stability is the improvement of the risk management program, which is based on a balanced system of formation and use of available resources. Aim and tasks. The aim of this paper is to explore the trends of risk management of modern investors in the selection of objects for placement of capital and formation a strategy of marketing management for the diversified businesses. The tasks of the paper are to research the theoretical aspects of risk management and planning; to analyze the risk management on the diversified companies; to develop solutions to improve the system of marketing management on the diversified companies in the context of risk management. Results. Investment marketing activities are one of the main ways to develop and increase the competitiveness of the economy and the individual companies operating in it. Marketing activities allow you to attract investments that support the implementation of the company's development strategy, increase its assets, develop innovative products, enter promising markets, ensure development in a highly competitive environment and stimulate the company's capitalization in the future. The dynamic growth of a diversified company is largely possible through diversification of investment capital and raising investment funds through the placement of shares in the financial market. An increase in the investment efficiency of a diversified company is possible only if there is a system of control over the economic activities of its individual business lines, otherwise it is highly likely that irrational investment decisions will be made and investment capital eroded due to the lack of proper control over its planning, placement and subsequent management. Conclusions. Modern diversified enterprises have to show investors that firms are in the sphere of financial management. This will help with the main risk of diversification – undervaluing by fund market. Modern conglomerates on the one hand should be present in the most popular industries among investors like technologies or bioengineering but on the other hand they have to concentrate its activity on the principles of private equity or leveraged buyout firms. It means that firms have to actively use loan capital after the recession and use their equity as more conservative as possible. It will allow getting financial results as good as private equity funds but for the public conglomerates it will allow to keep present investors and to attract new ones with conservative strategy.